2019
DOI: 10.2478/fv-2019-0030
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mastitis on Reproductive Parameters of Dairy Cows

Abstract: The aim of this study was to evaluate the occurrence of mastitis and its impact on the reproductive parameters in a herd of 180 dairy cows. Based on the herd records 127 cows of Slovak spotted cattle and their crosses with red Holstein were selected for study between 1—2 months after calving. The examination of the health status of the mammary glands consisted of: the clinical examination of the udder, the California mastitis test (CMT) supplemented by the collection of mixed milk samples, and the laboratory e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
(7 reference statements)
2
4
0
Order By: Relevance
“…The present results agreed with those reported by Miller et al (2001) and Villa-Arcilaa et al (2017), who found that the post-partum first service in dairy cows was higher (86, 94,days) in those cows with mastitis (clinical or subclinical) than (71, 84, days) in healthy cows. Similar trend was observed by Zigo et al (2019) who found that the first post-partum service was 61.5, 66, and 85 days in healthy cows, sub-clinical mastitis, and clinical mastitis in dairy cows, respectively. When compared to control cows, Jersey cows with clinical mastitis before first service had a 22.6 day increase in first service post-partum (Barker et al, 1998).…”
Section: Postpartum First Service Intervalsupporting
confidence: 87%
See 3 more Smart Citations
“…The present results agreed with those reported by Miller et al (2001) and Villa-Arcilaa et al (2017), who found that the post-partum first service in dairy cows was higher (86, 94,days) in those cows with mastitis (clinical or subclinical) than (71, 84, days) in healthy cows. Similar trend was observed by Zigo et al (2019) who found that the first post-partum service was 61.5, 66, and 85 days in healthy cows, sub-clinical mastitis, and clinical mastitis in dairy cows, respectively. When compared to control cows, Jersey cows with clinical mastitis before first service had a 22.6 day increase in first service post-partum (Barker et al, 1998).…”
Section: Postpartum First Service Intervalsupporting
confidence: 87%
“…In addition, Khokon et al (2017) found that 47 to76%, cases was positive to California Mastitis Test (CMT) in dairy cows. Recently, Zigo et al (2019) recorded that percentage of subclinical mastitis cases was 15.7 %,but clinical forms was 4.7 % in dairy cows.…”
Section: Postpartum Incidence Rate Of Clinical and Subclinical Mastitismentioning
confidence: 99%
See 2 more Smart Citations
“…lobally, cattle breeds are given a greatest interest in the farmer's work due to their high milk production and recurrent pregnancy and producing calf (1). Local Iraqi cow breed is one of the most important animals because of considering of them as a main source of milk and meat production which are essential components of human nutrition.…”
Section: Introductionmentioning
confidence: 99%